Analysis of cross section and astrophysical S-factor at low energies - Abdul Aziz, Azni; Abu Kassim, Hasan; Zamrun, Muhammad F. (American Institute of Physics, 2013)
Experimental measurements of cross section, σ(E) at very low energies are mainly not available. The rates can be calculated by extrapolation of the astrophysical S-factor to very low energies or determination of the cross section using theoretical models. In this work, we compare the cross section from the theoretical models and experimental data and obtain the best extrapolation of the astrophysical S-factor.